Efficiency of the enterprise resource potential - Sikorska, Małgorzata; Pererva, P. G.; Kiss, Kristina (Національний технічний університет "Харківський політехнічний інститут", 2018)
The economic value of the results obtained is to improve the methodological approaches to the diagnosis of the resource potential of light industry enterprises and the further development of theoretical aspects of the diagnosis of the enterprise.
Keywords: potential; technical progress; enterprise; efficient